2019
DOI: 10.1109/access.2019.2939490
|View full text |Cite
|
Sign up to set email alerts
|

Network Security Situation Prediction Based on MR-SVM

Abstract: The support vector machine (SVM) is verified to be effective for predicting cyber security situations, however, the long training time of the prediction model is a drawback to its use. To address this, a cyber security situation prediction model based on MapReduce and the SVM is proposed. The base classifier for this model uses an SVM, and parameter optimization is performed by the Cuckoo Search (CS) to determine the optimal parameters of the SVM. Considering the problem of time cost when a data set is large, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Network security situation prediction means predicting the future network situation according to the current network state and historical data. In recent years, the rapid development of machine learning provides a new solution for network situation prediction, such as the support vector machine (SVM) [ 12 ] and hidden Markov model (HMM) [ 13 ]. Then, deep learning applies to network security situation assessment: for example, [ 14 ] summarizes the artificial intelligence related to network security as well as the progress and challenges of current research; [ 15 ] studies the performance of different neural networks in the NSSP; and [ 16 ] proposes an LSTM network security situation prediction model based on the sigmoid weighted reinforcement mechanism, which can improve the convergence rate.…”
Section: Related Workmentioning
confidence: 99%
“…Network security situation prediction means predicting the future network situation according to the current network state and historical data. In recent years, the rapid development of machine learning provides a new solution for network situation prediction, such as the support vector machine (SVM) [ 12 ] and hidden Markov model (HMM) [ 13 ]. Then, deep learning applies to network security situation assessment: for example, [ 14 ] summarizes the artificial intelligence related to network security as well as the progress and challenges of current research; [ 15 ] studies the performance of different neural networks in the NSSP; and [ 16 ] proposes an LSTM network security situation prediction model based on the sigmoid weighted reinforcement mechanism, which can improve the convergence rate.…”
Section: Related Workmentioning
confidence: 99%
“…The authors used seeker optimization algorithm to find the best weight and introduced simulated annealing algorithm to improve the global search ability of the algorithm, but BP neural network is not suitable for time series data. Hu et al [6] proposed a situation prediction algorithm of SVM based on MapReduce to solve the problem that the training time of SVM is long when there are a large number of samples. Compared with the traditional model, this prediction model improves the prediction accuracy and reduces the training time.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that the method had more accurate prediction results, although the training time was long. Aiming at the problem of long training time of the support vector machine (SVM) algorithm, Hu et al [11] optimized the SVM algorithm with the cuckoo search (CS), carried out distributed training on MapReduce, and found that the method could effectively reduce the training time. Zhou et al [12] solved the NSSP problem with the hidden belief rule base (HBRB), improved the prediction accuracy of the model based on the evidence reasoning rules, and verified the effectiveness of the new method by the case study.…”
Section: Introductionmentioning
confidence: 99%